Hydropolitics in the Indus Basin - The Indus Waters Treaty and Water Mismanagement in Pakistan. - Sattar, Uzair; Bhargav, Atrey. (Tufts University. Tisch Library., 2019)
Paper written for the Tufts Institute for Global Leadership. Published in Yale Review of International Studies.